Optimalisasi Penggunaan Sarana Praktek Boga sebagai Laboratorium di SMK N 30 Jakarta untuk Meningkatkan Hasil Belajar Mata Pelajaran Tata Hidang Bagi Siswa Kelas X - Komariah, Komariah (Universitas Pendidikan Ganesha, 2018)
The purpose of this Classroom Action Research is to improve student learning outcomes in Tata Boga subjects for students of class X Even Semester of State Vocational School 30 Jakarta 2014/2015 Academic Year Jakarta. This research was conducted in August 2014 where the research subjects were students of class X Even Semester of State Vocational School 30 Jakarta 2014/2015 Academic Year. This research is a classroom action research conducted in two cycles. Each cycle consists of 2 meetings which consist of planning, action, observation, evaluation, and reflection. Data on student learning outcomes are collected through tests. The collected data was analyzed using descriptive analysis. The results of this study are in the first cycle, with an average value reaching 78.28 while in the second cycle the average value is 82.94. Based on the findings from the results of this Classroom Action Research, it can be concluded that optimizing the use of food practice facilities as a learning laboratory is proven to improve student learning outcomes for Tata Hidang subjects with Tata Basic Lover material, for students of class X Even Vocational Semester Negeri 30 Jakarta in Academic Year 2014/2015.